Exposure to air pollution in critical prenatal time windows and IgE levels in newborns - Herr, Caroline E W; Ghosh, Rakesh; Dostal, Miroslav; Skokanova, Venuse; Ashwood, Paul; Lipsett, Michael; Joad, Jesse P; Pinkerton, Kent E; Yap, Poh-Sin; Frost, Joshua D; Sram, Radim; Hertz-Picciotto, Irva (Pediatric allergy and immunology, 2011)
The objective of this study was to analyze the mechanisms by which exposure to ambient air pollutants influences respiratory health may include altered prenatal immune development. To analyze associations between elevated cord serum Immunoglobulin E (IgE) levels and maternal air pollution exposure during each month of gestation. Total cord serum IgE was determined by the CAP system and mothers' total IgE levels by nephelometry for 459 births in the Czech Republic from May 1994 to mid-January 1997. Concentrations of polycyclic aromatic hydrocarbons (PAHs) and particulate matter <2.5 microns in diameter (PM(2.5) ) were measured in ambient air, and arithmetic means were calculated for each gestational month. Log binomial regression models were used to estimate prevalence ratios (PR) for elevated cord serum IgE (≥0.9 IU/ml) adjusting for district of residence, year of birth, and in further models, for maternal IgE (a surrogate for atopy) and gestational season. Heterogeneity by maternal atopy status was evaluated for associations of air pollution and of cigarette smoke. In adjusted models, PAH and PM(2.5) exposures in the second month of gestation were each associated with a lower prevalence of elevated cord serum IgE. For an average increase of 100 ng/m(3) of PAHs, the PR was 0.69 (95% confidence interval (CI): 0.50, 0.95); for 25 μg/m(3) increase in PM(2.5) , the PR was 0.77 (95% CI: 0.55, 1.07). Conversely, exposures later in gestation were associated with a higher prevalence of elevated cord IgE: in the fifth month, the PR for PAH exposure was 1.64 (95% CI: 1.29, 2.08), while for PM(2.5) in the sixth month, it was 1.66 (95% CI: 1.30, 2.13). In analyses stratified by maternal atopy, air pollutants were associated with altered cord serum IgE only among neonates with non-atopic mothers. Similarly, an association of cigarette smoke with elevated cord serum IgE was found only in non-atopic mothers. PAHs and PM(2.5) , constituents of both ambient air pollution and cigarette smoke, appear to influence fetal immune development, particularly among infants whose mothers are not atopic.
Keywords: Young Adult; Prenatal Exposure Delayed Effects; Male; Particulate Matter; pevné částice; zpožděný efekt prenatální expozice; mladý dospělý; gestační stáří; Immunoglobulin E; Česká republika; Gestational Age; Pregnancy; těhotenství; Adult; dospělí; mužské pohlaví; Air Pollution; Smoking; fetální krev; polycyklické aromatické uhlovodíky; látky znečišťující vzduch; Fetal Blood; Czech Republic; novorozenec; znečištění ovzduší; lidé; ženské pohlaví; Humans; imunoglobulin E; Infant, Newborn; Environmental Exposure; Female; kouření; Polycyclic Aromatic Hydrocarbons; vystavení vlivu životního prostředí; Air Pollutants